Job Insecurity, Work-Related Flow, and Financial Anxiety in the Midst of COVID-19 Pandemic and Economic Downturn - Basyouni, Sawzan Sadaqa; El Keshky, Mogeda El Sayed (Frontiers in Psychology, 2021)
During the COVID-19 pandemic, every domain of industry has experienced a severe economic downturn with concomitant stress throughout the economy. Employees working in government and private sectors are experiencing different psychological problems. The current study was conducted to investigate the role of work-related flow in the relationship of job insecurity with financial anxiety in the employees working in private and government sectors of Saudi Arabia. The sample comprised 1195 employees, 886 females and 309 males. The participants’ ages ranged from 25 to 60 years. The Financial Anxiety Scale, Work-Related Flow Inventory, and Qualitative Job Insecurity Measures were found valid and reliable. Structural equation modeling was applied to test the associations. As hypothesized, the results indicated that job insecurity was positively related to financial anxiety, work-related flow was negatively associated with financial anxiety, and work-related flow mediated the relationship between job insecurity and financial anxiety. All these associations were significant regardless of gender, age, marital status, sector of employment, income, self-rated health, and COVID-19 infection status. Further research is needed to understand the impact of job insecurity on financial anxiety in-depth through the paths of work-related flow, especially in the midst of COVID-19.